Serum Fibrinogen Level and Cytokine Production as Prognostic Biomarkers for Idiopathic Sudden Sensorineural Hearing Loss. Issue 7 (7th August 2022) - Okuda, Hiroshi; Aoki, Mitsuhiro; Ohashi, Toshimitsu; Ogawa, Bakushi; Shibata, Hirofumi; Ueda, Natsuko; Hayashi, Hisamitsu; Nishihori, Takezumi; Kuze, Bunya; Ohnishi, Hidenori; Ogawa, Takenori
Abstract : Objectives: No clinically useful prognostic factors have been identified for idiopathic sudden sensorineural hearing loss (ISSNHL). The current study therefore sought to identify useful prognostic factors for idiopathic sudden sensorineural hearing loss from blood biomarkers while attempting to classify the pathogenic mechanism and formulate treatment strategies based on these results. Study Design: Prospective cohort study. Setting: Tertiary referral center. Methods: A total of 47 patients with acute phase ISSNHL were treated with steroid at an initial dose of 1 mg/kg/day and hyperbaric oxygen therapy and followed up for 6 months. Serum fibrinogen levels, peripheral blood mononu- clear cells (PBMCs), and interleukin (IL)-1β, IL-6, and tumor necrosis factor (TNF)-α production levels from PBMCs were measured, after which patient's pre- and post- treatment hearing was compared. Results: In the overall cohort, the mean improvement level, mean recovery rate, and mean fibrinogen level was 20.3 dB, 46.2%, 292.0 mg/mL, respectively. The mean levels of IL-1β, IL-6, and TNF-α produced by peripheral blood mononu- clear cells cultured under lipopolysaccharide stimulation were 318.4, 498.1, and 857.6 pg/mL, respectively. High fibrinogen levels were associated with poor hearing progno- sis. Lipopolysaccharide-stimulated cytokine production by PBMCs did not correlate with hearing changes; however, the prognosis was significantly better in patients with low fibrinogen levels and high IL-1β levels produced by PBMCs than in other patients. Conclusions: Our results suggest that patients with simple inflammatory-type ISSNHL responded well to standard therapy. Therefore, serum fibrinogen levels and PBMCs cytokine production may help determine the management of ISSNHL based on its pathogenic mechanism.